Narzędzia identyfikacji zdolności do nauki języków obcych, ich analiza i możliwości zastosowania w glottodydaktyce - Sobańska-Jędrych, Joanna (Neofilolog, 2010)
Diagnosis is one of teachers’ (including foreign language teachers) key tasks. The teacher should get to know his or her learners and their intellectual abilities before beginning the process of developing their language competence. Unfortunately, Polish teachers lack standard tools of measuring foreign language learning aptitude. Such a situation follows from insufficient knowledge in this field. Another reason is the scarcity with which this issue is discussed. The aim of this article is to discuss the ways of diagnosing foreign language learning aptitude that have been attempted so far both in Poland and abroad. This will constitute the background for the analysis of the present tools for measuring foreign language learning aptitude and the possibilities of applying them in research into foreign language learning and teaching. This analysis takes as a point of reference the current theory of abilities involved in learning a foreign language.